Rapid cognitive assessment: Accuracy and discriminant validity of Mini-Cog and process-based Clock Drawing Test - Yang, Qian; Yang, Hao; Long, Wei; Zuo, Sheng; Zhu, Defa; Guo, Qihao (Journal of Alzheimer's disease, 2025)
BackgroundThe Mini-Cog is a brief cognitive examination comprising a three-item memory recall and a simplified Clock Drawing Test (CDT). There is limited research on the effects of detailed scoring criteria for the Mini-Cog on cognitive screening.ObjectiveTo assess the diagnostic effectiveness of three Mini-Cog versions and a new process-based CDT test in identifying mild cognitive impairment (MCI) and Alzheimer's disease (AD) compared to cognitively normal controls (NC).MethodsWe prospectively enrolled 950 subjects who underwent standardized neuropsychological assessments and the Mini-Cog test. The CDT was scored using an adapted 10-point scale. The accuracy of three Mini-Cog versions (Mini-Cog1: 3-word delayed recall + 2-point CDT; Mini-Cog2: 3-word immediate recall + 3-word delayed recall + 3-point CDT; Mini-Cog3: 3-word immediate recall + 3-word delayed recall + 10-point CDT) was assessed through the receiver operating characteristic analysis. Sensitivity and specificity were determined for each diagnostic threshold.ResultsThe optimal cut-off point for Mini-Cog3 is 12/16 for MCI and 10/16 for AD. Mini-Cog3 demonstrated the highest diagnostic efficacy, with AUCs of 0.82 (95% CI: 0.78-0.85) for MCI and 0.95 (95% CI: 0.94-0.97) for AD, with sensitivity of 85% for both MCI and AD. The CDT's AUCs were 0.77 (95% CI: 0.73-0.81) for MCI, and 0.87 (95% CI: 0.84-0.90) for AD, with sensitivity of 89% for MCI, and 82% for AD.ConclusionsA more elaborate scoring system, such as Mini-Cog3, may serve as an effective screening method for the rapid and accurate detection of cognitive dysfunction in patients with MCI and AD.